2002
DOI: 10.1046/j.1468-3148.2002.00143.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Group Intervention on the Relationships of Parents with Intellectual Disabilities

Abstract: Background  Parents with intellectual disabilities frequently feel socially excluded and often become dependent on statutory agencies for support. This study aimed to tackle these difficulties by means of a group intervention. Methods  Group intervention was provided to 12 parents with borderline or mild intellectual disabilities over 14 weeks. The effects of intervention were evaluated by comparing the intervention group with a borderline or mild intellectual disabilities control parent group (n = 10). Both e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 21 publications
(30 reference statements)
3
56
0
2
Order By: Relevance
“…Psychological therapy for interpersonal functioning was not supported by the analysis of data from Matson and Senatore (1981) and McGaw et al (2002). Results are inconsistent from these studies and hence do not provide sufficient evidence that treatment is efficacious, as evidenced by the negative effect of g = -0.342, 95% CI [-.946, .262], N = 43.…”
Section: Meta-analysesmentioning
confidence: 90%
See 1 more Smart Citation
“…Psychological therapy for interpersonal functioning was not supported by the analysis of data from Matson and Senatore (1981) and McGaw et al (2002). Results are inconsistent from these studies and hence do not provide sufficient evidence that treatment is efficacious, as evidenced by the negative effect of g = -0.342, 95% CI [-.946, .262], N = 43.…”
Section: Meta-analysesmentioning
confidence: 90%
“…McGaw, Ball, and Clark (2002) and Silvestri (1977) reported an average IQ in the borderline IDs range for their intervention groups, whilst Dowling, Hubert, White, and Hollins (2006) included people with "severe" IDs. However, the majority of studies included samples of people with "mild" IDs.…”
Section: Methodological Issuesmentioning
confidence: 99%
“…Mental health professionals while working with families should strengthen the social network and support systems, which would help them overcome the stress and negative attitude towards their children with learning disability. Research has found a strong association between supportive social networks and the positive psychological well-being of parents of children with learning disabilities (McGaw et al, 2002;Kroese et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Parents often socially excluded and may depend on statutory agencies for support (McGraw et al, 2002). To avoid labelling as 'in need', parents may reject not seek help (Ward and Tarleton, 2007).…”
Section: Findings: Women With Ldmentioning
confidence: 99%